Neurological complications following pediatric allogeneic hematopoietic stem cell transplantation: Risk factors and outcome - Zaidman, Irina; Shaziri, Tamar; Averbuch, Dina; Even-Or, Ehud; Dinur-Schejter, Yael; NaserEddin, Adeeb; Brooks, Rebecca; Shadur, Bella; Gefen, Aharon; Stepensky, Polina (Frontiers in Pediatrics, 2022)
Background Allogeneic hematopoietic stem cell transplantation (HSCT) is an efficient treatment for numerous malignant and nonmalignant conditions affecting children. This procedure can result in infectious and noninfectious neurological complications (NCs). Objective The objective of the study is to examine the incidence, risk factors, and outcomes of NCs in pediatric patients following allogeneic HSCT. Methods We performed a retrospective study of 746 children who underwent 943 allogeneic HSCTs in two large pediatric hospitals in Israel from January 2000 to December 2019. Results Of the pediatric patients 107 (14.3%) experienced 150 NCs. The median follow-up was 55 months. Noninfectious NCs were more common than infectious NCs (81.3% vs. 18.7%). Factors significantly associated with type of NC (infectious vs. noninfectious) were underlying disease (immunodeficiency vs. malignant and metabolic/hematologic disease) (p-value = 0.000), and use of immunosuppressive agent, either Campath or ATG (p-value = 0.041). Factors with a significant impact on developing neurological sequelae post-NC were number of HSCT >1 (p-value = 0.028), the use of alemtuzumab as an immunosuppressive agent (p-value = 0.003), and infectious type of NC (p-value = 0.046). The overall survival rate of whole NC-cohort was 44%; one-third of all mortality cases were attributed to the NC. The strongest prognostic factors associated with mortality were older age at HSCT (p-value = 0.000), the use of alemtuzumab as an immunosuppressive agent (p-value = 0.004), and the existence of neurological sequelae (p-value = 0.000). Abnormal central nervous system imaging (p-value = 0.013), the use of alemtuzumab as an immunosuppressive agent (p-value = 0.019), and neurological sequelae (p-value = 0.000) had statistically significant effects on neurological cause of death. Conclusion Infectious and noninfectious NCs are a significant cause of morbidity and mortality following allogeneic HSCT in children. Further research is required to better understand the risk factors for different NCs and their outcomes regarding sequelae and survival.